2018
DOI: 10.1016/j.jvscit.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Renal artery aneurysm associated with Leber hereditary optic neuropathy

Abstract: Leber hereditary optic neuropathy is an inherited, rare, mitochondrial metabolic disease that leads to progressive vision loss due to the accumulation of reactive oxygen species. The disorder has been associated with microangiopathy and macroangiopathy. We present a novel case of saccular left renal artery aneurysm in a 27-year-old man with known Leber hereditary optic neuropathy. The lesion was asymptomatic and grew from 1.8 to 2.0 cm during the course of 1 year. We successfully performed an endovascular left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…The ratio of different subtypes of optic neuritis (ON) was higher than the other diseases; we analyzed the reason may be our center is the neuro-ophthalmology department, while the other centers are the neurology department. We also found LHON accompanied with IOIS and compression optic neuropathy, which were unreported before; only Jones et al (2018) reported a case of saccular left renal artery aneurysm in a 27-year-old man with known LHON.…”
Section: Discussionsupporting
confidence: 71%
“…The ratio of different subtypes of optic neuritis (ON) was higher than the other diseases; we analyzed the reason may be our center is the neuro-ophthalmology department, while the other centers are the neurology department. We also found LHON accompanied with IOIS and compression optic neuropathy, which were unreported before; only Jones et al (2018) reported a case of saccular left renal artery aneurysm in a 27-year-old man with known LHON.…”
Section: Discussionsupporting
confidence: 71%